Callus Induction and In vitro Regeneration from Leaf and Cotyledon Explants of Noni (Morinda citrifolia L.) (Plant Tissue Culture and Biotechnology, 2026)
Noni (Morinda citrifolia L.) is considered as an important medicinal plant due to its medicinal properties. In this study, young leaves and cotyledons of Noni were used as explants for callus induction on MS medium supplemented with different concentrations of 2,4-D (1.0-5.0 mg/l). The results demonstrated that both leaf and cotyledon explants exhibited the maximum callus induction on MS medium supplemented with 3.0 mg/l 2,4-D. Here cotyledon explants showed better performance on callus induction than that of leaf explants. For the enhancement of plantlet regeneration, induced calli were transferred to MS0, ½MS0, and ¼MS0 medium  where different concentrations and combinations of BAP (1.0-5.0 mg/l), Kn (0.5-2.5 mg/l) and NAA (0.2-1.0 mg/l) were used either single or in combination. Results showed that ½MS0 medium produced the best performance on regeneration (79.76%). Calli derived from cotyledons showed better regeneration ability than that of the leaves. Consequently, proliferation of shoots (9.10.50) from cotyledon derived callus were formed to be higher than that of leaf segment derived callus (5.6). MS medium with 4.0 mg/l BAP and 2.0 mg/l Kn produced the best results in increasing shoot length (4.020.22 cm). Here ½MS0  medium supplemented with 2.0 mg/l IBA showed the best performance on root induction (93.801.78) and increasing the length of roots (1.760.03 cm).Plant Tissue Cult. & Biotech. 36(1): 01-11, 2026 (June)